Bättre åtkomst till avverkningstrakter med anpassat marktryck från avverkningsmaskinerna - Andersson, Erik (2010)
The global climate-change means increasing mean-temperature and higher precipitation in Sweden, which leads to shorter periods of frozen ground in the forest. At the same time the harvesting machines are getting bigger and more powerful. The forest industry aim at an even wood flow, and the ground damage has to be as low as possible. The two biggest causes for ground-damage is the bearing capacity of the forest ground and the ground-pressure of the harvesting machines. The aim of this study was to find out some rules for the machine choice considering ground pressure, when harvesting on ground with low bearing capacity.